Origin and mixing of crude oils in Triassic reservoirs of Mahu slope area in Junggar Basin, NW China: Implication for control on oil distribution in basin having multiple source rocks. (December 2016) - Chen, Zhelong; Liu, Guangdi; Wang, Xulong; Gao, Gang; Xiang, Baoli; Ren, Jiangling; Ma, Wanyun; Zhang, Qiong
Abstract: The origin of crude oils and their varied geochemical features along the western and northern slope of the Mahu depression in the Junggar Basin has been controversial. Based on the molecular and isotopic geochemistry of hydrocarbons from 46 drill-stem test crude oil samples and 36 core samples, three oil groups (I, II, III) and five subgroups (I1, I2, II, III1 and III2 ) have been recognized and oil-source correlations have been established. The subgroup I1 oils originated mainly from lower Permian Fengcheng (P1 f) carbonate source rocks, subgroup I2 from P1 f mudstone source rock and group II oils from Middle Permian Wuerhe (P2 w) mudstone source rock whose potential was underestimated in the past. Group III consists of mixed oils, i.e., subgroup III1 received contributions from P1 f carbonates and P2 w mudstones and subgroup III2 is a mixture of oils from P1 f mudstones and P2 w-generated oils. In order to determine the main source rocks, the laboratory oil mixing experiments were carried out. Tricyclic terpane biomarker parameters (TTs) were used to quantify the source contributions. Whole oil carbon isotope ratios were also used to verify the proportions of different oils in each mixture. The results show that subgroup III1 oils have diverse mixing ratios in different reservoir, subgroup III2 oils are mainly from P1 f mudstones and P2 w source rock contributes little. Finally, the accumulation process of oil fields along the northern slope of the Mahu depression was analyzed and the contributions from different sources were revealed. This study provides an effective quantitative method to identify contributions from different lacustrine source rocks to mixed oils in the Mahu depression, which could be helpful in predicting location and composition of undiscovered oils. Highlights: Tricyclic terpanes can be used to characterize crude oils in the Mahu depression. Oil-source correlations were established by biomarkers and carbon isotopes. Artificial mixing experiments were carried out to quantify the source contributions. The oil mixing process and source control on oil group distribution was evaluated.